An overview of the national cattle health- and welfare-related information systems in Estonia, Finland, Sweden, and Germany - Kallio, Tuija; Timonen, Anri; Tamm, Hardi; Põder, Anne; Kukk, Martin; Schlereth, Natascha; Ulvenblad, Pia; Ulvenblad, Per-Ola; Tikkanen, Elisa; Kilpeläinen, Pekka; Barth, Henrik; Abate Kassa, Getachew; et al. (Frontiers in Animal Science, 2025)
The digitalization of cattle husbandry has increased the cattle health- and welfare-related data creation and collection into multiple information systems (IS). We describe nationally the widely used cattle health and welfare data-containing IS in Estonia, Finland, Germany, and Sweden by studying their ownership and the funding, developmental views, data access, data ownership, and data integration between other IS. In addition, we describe the IS with experts and stakeholders in interviews and living labs (LLs). There are two statutory IS in each study country, while there is one non-statutory IS in Estonia and Sweden and four in Finland and Germany. The IS providers and the data integration possibilities between systems differed by study countries, while the type of data collected and the IS funding policies remained similar. In LLs, congruent views about the importance of the standardization of the collected data and the usability of these data for farm decision-making and improvement in management practices were mentioned as the main challenges for future development. To gain full benefit from the collected data, data from automatic milking systems should be integrable with the data collected into other IS. In the future, data integration should be improved for a more user-friendly approach of cattle health- and welfare-related IS, and utilization of the collected data for animal health and welfare improvement should be implemented within the cattle value chain to ensure the sustainability of the industry. Common will between public and private operators, as well as cross-border multidisciplinary cooperation, is required to fulfill these goals.